Development of a web-based decision support tool for sustainable residential building design and retrofit - Mangan, Suzi Dilara (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2021)
The development of tools that provide support to decision-makers for the sustainable design and retrofit of residential buildings is an important element of awareness-raising roadmaps focussed on reducing the current efficiency gap in the building sector. Many alternative designs that pertain to sustainable residential building production within this context have been proposed and are currently being developed. However, difficulty converting these design alternatives into informed design interventions can compromise the decision-making process. Therefore, we aimed to develop a web-based decision support tool that would take access to multiobjective design solutions one step further. Our tool integrates a feedback loop that overlaps with the principle of early design exploration and iteration into sustainable residential building production. In line with this aim, we propose an integrated workflow framework based on: i) a computational performance-based design support approach to enable the systematic and comprehensive evaluation and analysis of the design space and to determine optimal solutions, and ii) an interactive visualisation method to provide rapid and constructive feedback to decisionmakers on the broad design space obtained with this approach through an easy-to-use interface. We developed an energy- and cost-oriented decision support tool prototype with a highly informative capacity that facilitates decision-making processes regarding the design and retrofit of sustainable residential buildings based on this proposed framework. The decision-making process support potential of this tool can be adapted to the Turkish context. It has been presented to the Istanbul province, where significant urban growth is ongoing.
Keywords: Performance-based design; decision support tool; building performance simulation; data visualisation; residential buildings; ENERGY; SIMULATION; BARRIERS; COST; Engineering